Activation of virus uptake through induction of macropinocytosis with a novel polymerizing peptide. Issue 1 (4th October 2013) - Daniels, Sarah I.; Soule, Erin E.; Davidoff, Katharine S.; Bernbaum, John G.; Hu, Duosha; Maeda, Kenji; Stahl, Stephen J.; Naiman, Nicole E.; Waheed, Abdul A.; Freed, Eric O.; Wingfield, Paul; Yarchoan, Robert; et al.
Abstract : A 27‐aa peptide (P27) was previously shown to decrease the accumulation of human immunodeficiency virus type 1 (HIV‐1) in the supernatant of chronically infected cells; however, the mechanism was not understood. Here, we show that P27 prevents virus accumulation by inducing macropinocytosis (MPC). Treatment of HIV‐1‐ and human T‐cell lymphotropic virus type 1 (HTLV‐1)‐infected cells with 2–10 μM P27 caused cell membrane ruffling and uptake of virus and polymerized forms of the peptide into large vacuoles. As demonstrated by electron microscopy, activation of MPC did not require virus or cells infected with virus, as P27 initiated its own uptake in the absence of virus. Inhibitors of MPC, Cytochalasin D and amiloride, decreased P27‐mediated uptake of soluble dextran and inhibited P27‐induced virus uptake by >60%, which provides further evidence that P27 induces MPC. In CD4 + HeLa cells, HIV‐1 infection was enhanced by P27 up to 4‐fold, and P27 increased infection at concentrations as low as 20 nM. The 5‐aa C‐terminal domain of P27 was necessary for virus uptake and may be responsible for the polymerization of P27 into fibrils. These forms of P27 may play a key role in triggering MPC, making this peptide a useful tool for studying virus uptake and infection, as well as MPC of other macromolecules.—Daniels, S.I., Soule, E.E., Davidoff, K.S., Bernbaum, J.G., Hu, D., Maeda, K., Stahl, S.J., Naiman, N.E., Waheed, A.E., Freed, E.O., Wingfield, P., Yarchoan, R., Davis. D.A. Activation of virus uptake through induction of macropinocytosis with a novel polymerizing peptide. FASEB J . 28, 106–116 (2014). www.fasebj.org